Expectations of Agricultural Extension from Union Budget 2019 - Singh, A K (Indian Farming, 2019)
A robust and efficient extension system which is capable of meeting the evolving needs of farmers in the context of changing agricultural scenario is the need of the hour to enhance farmers’ income and also ensure a sustainable growth of agricultural sector. Investment in reviving extension system would serve in infusing dynamism into the stagnating graph of agricultural growth in India. The scope of agricultural extension has expanded well beyond its traditional role in pushing the frontiers of production and productivity in pursuit of the nation’s and food security. So now it is time to strengthen the structural framework of extension system to fulfil its ever widening scope.